THE TRACING THE INTERNALIZATION OF ADAB IN ISLAMIC EDUCATION PERSPECTIVE OF SYED MUHAMMAD NAQUIB AL ATTAS - Nurdiana; Hayani, Aida; Zulfikar Habibullah, Ahmad; Salim, Ahmad (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
Islam is veiled by the behavior of Muslims themselves). However, the Islamic world today, due to historical reasons in the last few centuries which is understandable, does indeed give a lot of negative impressions in the minds of non-Muslims, such as authoritarian and anti-democratic, anti-Western and progress, tendencies towards violence, corruption, and poverty. , and retarded. All the problems that have been described above are directly or indirectly related to the quality or product of education. Referring to the goals of Indonesian National Education; The method in this research is literature study. The results showed thatThe word Ta'dib according to Naquib Al-Attas is a term that is closer to the understanding of science. Or in other words, Ta'dib is understood as an educational term that emphasizes knowledge (science). In its conceptual structure, ta'dib includes elements, knowledge (science), teaching (ta'lim) and good parenting (tarbiyah). Therefore, it is no longer necessary to refer to the concept of education in Islam as tarbiyah, ta'lim and ta'dib all at once. Therefore, ta'dib is the most appropriate and accurate term for the term education in the Islamic sense.